2019
DOI: 10.1016/j.cell.2019.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Allosteric Ligand Recognition in the Human CC Chemokine Receptor 7

Abstract: Summary The CC chemokine receptor 7 (CCR7) balances immunity and tolerance by homeostatic trafficking of immune cells. In cancer, CCR7-mediated trafficking leads to lymph node metastasis, suggesting the receptor as a promising therapeutic target. Here, we present the crystal structure of human CCR7 fused to the protein Sialidase NanA by using data up to 2.1 Å resolution. The structure shows the ligand Cmp2105 bound to an intracellular allosteric binding pocket. A sulfonamide group, characteristic fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(135 citation statements)
references
References 59 publications
2
115
0
3
Order By: Relevance
“…So far, four small molecules have been validated by crystallography to bind at this position. The targets are three chemokine receptors (CCR2, PDB code: 5T1A 192 ; CCR7, PDB code: 6QZH 193 ; and CCR9, PDB code: 5LWE 194 ) and β 2 AR (PDB code: 5X7D 195 ). These ligands are all NAMs and proximately share the same binding site (TM1, TM2, TM6, TM7, ICL1, and H8).…”
Section: Gpcr Pharmacologymentioning
confidence: 99%
“…So far, four small molecules have been validated by crystallography to bind at this position. The targets are three chemokine receptors (CCR2, PDB code: 5T1A 192 ; CCR7, PDB code: 6QZH 193 ; and CCR9, PDB code: 5LWE 194 ) and β 2 AR (PDB code: 5X7D 195 ). These ligands are all NAMs and proximately share the same binding site (TM1, TM2, TM6, TM7, ICL1, and H8).…”
Section: Gpcr Pharmacologymentioning
confidence: 99%
“…These structures confirmed that chemokine receptors have the canonical 7‐transmembrane GPCR fold with the extracellular end of the TM helices forming a wide orthosteric pocket to accommodate ligand binding . The initial, antagonist‐bound, CXCR4 structures have since been followed by structures of CCR2, CCR5, CCR7, and CCR9 all bound to different small molecule ligands as well as a structure of CCR5 bound to the HIV protein GP120 determined by cryo‐EM …”
Section: Studies Of Chemokines With Full‐length Receptors: High Resolmentioning
confidence: 65%
“…Recently, it was reported that allosteric antagonism by small molecules under clinical investigation interfered with CCL19-driven signaling ( 195 ). Thus this work confirmed a long-standing interest in active synthetic drugs to avoid entry of cancer cells into LN.…”
Section: Ccr7 As a Novel Therapeutic Target In Cllmentioning
confidence: 99%